SINTESIS POLI (GLIKOLIDA-CO-LAKTIDA) DAN UJI BIODEGRADABILITASNYA - Rofiq Sunaryanto; Hardaning Pranamuda (Jurnal Kimia Terapan Indonesia, 2015)
Polylactide and polyglycolide are important aliphatic polyester consist of lactide and glycolide repeats unit. It is considered as green polymer due to it is produced from renewable agricultural resources. The development of biodegradable plastics based on agricultural resources is still important to be done. Copolymerization of glycolide with D-lactide, L-lactide, and DL-lactide using a Sn(Oct)2 as catalyst had been carried out. Polymerization was conducted by ring-opening of lactide and glycolide without the solvents but melting polymerization. Polymerization were conducted at 130 Â°C for 130 hours. Result of this study showed that polymerization of glycolide with D-lactide produce polymers with an average molecular weight of 8.2x103 and a yield of 72 %. Polymerization of glycolide with L-lactide produce polymer with an average molecular weight of 2.8x103 and a yield of 36 %. Polymerization glycolide with DL-lactide produce polymer with an average molecular weight of 2.5x103 with a 48 % yield. The burial test for 28 days showed poly (glycolide-co-Llaktida) degraded faster than other polymers, namely degraded 32 %. While poly (glycolide-co-DL-lactide) and poly (glycolide-co-D-lactide) showed similar degradation that is equal to 20 %. Compared with PHB (polyhydroxybutyrate), poly (glycolide-co-lactide) degraded more slowly.Keywords: Glycolide, lactide, copolymerization, biodegradable plastic